Behavior of ZnO nanoparticles in glycine solution: pH and size effect on aggregation and adsorption; Colloid and Interface Science Communications; Vol. 39 - Godymchuk (Godimchuk) A. Yu. Anna Yuryevna; Papina Yu. V. Yuliya Vladimirovna; Karepina E. E. Elizaveta Evgenjevna; Kuznetsov D. V. Denis Valerjevich (2020, 2020)
Title screen